Public Perception on The Implementation of Tax Amnesty Program - Remitasari, Adhitya; Fenton, Adam James (LSPR Institute of Communication & Business, 2021)
Expecting fairness living, prosperous and welfare life are some expectations of the citizen. Tax revenue becomes the national backbone of the state budget to finance the state expenditures. Many obstacles can challenge the target of tax revenue collection. This critical point needs an awareness collectively from all elements of the nation to get survive with a shortfall nation budget. One of the tax solutions is tax amnesty program becomes a national agenda. Tax amnesty program is expected could reach the huge tax target in 2016. Therefore, tax amnesty will greatly assist the government efforts to improve economic conditions, develop massive infrastructures, enhance the health quality, reduce unemployment, reduce poverty, and improve inequality. Those objectives should be conducted by the well-managed communication plan to socialize the tax amnesty program. The socialization can be delivered by seminar, forum group discussion, online newspapers, social media, personal email, website, etc. The various communication channels have been implemented to deliver the message to the public effectively. Accordingly, the aim of the study is to explore the public perception of tax amnesty, to figure out the effectivity of tax amnesty implementation. Tax amnesty would be more effective to embrace the taxpayers through persuasive approaches. This approach is more desirable. Taxpayers are accompanied as partners to cultivate their tax awareness. This research assessed that many taxpayers have less known regarding the tax amnesty. Indeed, taxpayers need to understand more deeply to the Tax Amnesty Program. Thus, it would conduct tax compliance manner eventually.